BUILDING DIGITAL CIVIC COMPETENCE IN INDONESIAN PRIMARY EDUCATION: A QUALITATIVE ANALYSIS OF SUSTAINABLE DEVELOPMENT GOAL INTEGRATION - Damanik, Prince Clinton Immanuel Christian; Ningsih, Kholifatul Novita; Pahlawaty, Neddyana; Kedhaton, Arum Sekar (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This qualitative investigation examines how Indonesian primary schools incorporate digital civic competence as a means of advancing Sustainable Development Goals 4 (Quality Education), 10 (Reduced Inequalities), and 16 (Peace, Justice, and Strong Institutions). Employing a descriptive qualitative approach with thematic analysis methodology, the research analyzes national educational frameworks, scholarly discourse, and institutional practices within the contexts of Kurikulum Merdeka, Profil Pelajar Pancasila, and Adiwiyata (Green School) initiatives. Results indicate growing integration of digital civic education through project-based learning, digital narrative approaches, and responsible online participation that cultivate learners' analytical capabilities and civic consciousness. Nevertheless, substantial obstacles remain, including insufficient educator capacity, disparate technological access across regions, and limited development of context-specific ethical guidelines. The research offers a novel theoretical framework by synthesizing Pancasila values with digital civic education and sustainability principles, positioning moral, civic, and technological literacy as interconnected elements within transformative pedagogical practice. This integrated perspective highlights the necessity for systematic policy execution, continuous professional learning for educators, and culturally responsive instructional approaches to foster inclusive, ethically grounded, and sustainable digital educational ecosystems consistent with SDG targets.